Stillbirth among women prescribed nicotine replacement therapy in pregnancy: analysis of a large UK pregnancy cohort - Dhalwani, Nafeesa N.; Szatkowski, Lisa; Coleman, Tim; Fiaschi, Linda; Tata, Laila J. (Oxford University Press, 2018)
Objective: To compare risk of stillbirth between maternal smokers and those prescribed NRT during pregnancy.